Intrahepatic Cholestasis of Pregnancy Increases Inflammatory Susceptibility in Neonatal Offspring by Modulating Gut Microbiota - Lin, Qiong-xi; Huang, Wan-wen; Shen, Wei; Deng, Xiao-shi; Tang, Zi-yu; Chen, Zhen-hui; Zhao, Wei; Fan, Hong-ying (Frontiers in Immunology, 2022)
Intrahepatic cholestasis of pregnancy (ICP) is a liver disease of pregnancy that is characterized by increased bile acid levels in maternal serum. Studies have shown that cholestatic pregnancy can result in long-term metabolic disturbances in the offspring. However, how ICP shapes the offspring’s immunity and predisposition to inflammatory disorders at an early stage is unknown. In this study, we investigated the effect of maternal cholestasis on neonatal offspring metabolism and immune function. We compared 71 neonates with ICP mothers and 63 neonates with healthy mothers and found that the incidence of jaundice and infection was significantly higher in ICP offspring. Maternal serum total bile acid level was associated with blood cell counts in full-term ICP offspring. In animal experiments, a compensatory activation of hepatic and ileal farnesoid X receptor (FXR) and altered gut microbiota in the first week were found in ICP offspring. We also investigated lipopolysaccharide (LPS)-induced inflammatory responses in neonatal rats and found that ICP offspring were more susceptible to inflammation. To understand the correlation between congenital abnormal FXR activation and tissue immunity dysregulation, we assessed the effects of the FXR agonist GW4064 and FXR antagonist E/Z-GS in ICP offspring after LPS exposure. The expression of several pro-inflammatory cytokines significantly decreased after treatment with E/Z-GS but increased after treatment with GW4064. Treatment with the probiotic Lactobacillus rhamnosus LRX01 that inhibits FXR expression in the ileum reduced susceptibility to LPS exposure in ICP offspring. The current study indicated that cholestatic pregnancy may increase the susceptibility of the offspring to inflammation by altering bile acid metabolism and gut microbiota at an early stage. We suggest that supplementation with Lactobacillus rhamnosus LRX01, which inhibits FXR expression in the ileum, may improve intestinal immunity in ICP offspring.